PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP KETERAMPILAN BERBICARA DALAM PELAJARAN BAHASA INDONESIA - KRISTINA AYU RAHMADANI; Abd Rahman Azahari; Widya Permata Dilla (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
Speaking is one of the essential language skills that elementary school students are expected to master in learning Indonesian. However, many students face difficulties in orally expressing ideas, especially when dealing with new vocabulary. This study aimed to investigate the effect of the Talking Stick learning model on the speaking skills of fifth-grade students at SDN 11 Langkai. This research employed a pre-experimental method using One-Group Pretest-Posttest Design. The study was conducted over three sessions on March 11, 13, and 18, 2025, involving 26 students of Class V-A. The research instrument was an oral test used to assess speaking skills. The collected data were analyzed using the Wilcoxon Signed-Rank Test, as the posttest data were not normally distributed. The instrument was validated through expert judgment by lecturers specialized in Indonesian Language Education. The findings revealed an improvement in the students’ average scores from 52.9 in the pretest to 80.4 in the posttest. The Wilcoxon test result showed a significance value of 0.000 (p < 0.05), indicating a significant effect of the Talking Stick model on students’ speaking skills. This model fostered active participation, boosted students’ confidence, and facilitated structured and contextual expression of ideas. Therefore, the Talking Stick learning model can be considered an effective approach to developing students’ speaking skills in elementary education.